High-conductivity three-dimensional carbon nano-wire modified composite phosphate material and preparation method thereof
The preparation of Na4(FexMny)3Mz(PO4)2P2O7/C material modified with high conductivity three-dimensional carbon nanowires was solved by a simple "one-pot method", which solved the problem of low electronic conductivity of existing materials, achieved high conductivity and structural stability of the material, and significantly improved the performance of the positive electrode material of sodium ion battery.
Patent Information
- Application Number
- CN202411951311.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing iron manganese-based sodium pyrophosphate materials have low electronic conductivity. Traditional improved methods such as surface carbon coating have problems such as discontinuous conductive network, uneven carbon layer thickness, and uneven distribution of doped atoms, making it difficult to significantly improve the electronic conductivity of the material.
Na4(FexMny)3Mz(PO4)2P2O7/C material modified with high conductivity three-dimensional carbon nanowires was prepared by a simple "one-pot method". High conductivity three-dimensional carbon nanowires were introduced in situ using ordinary carbon sources, and doped ions M were introduced into the solution to achieve uniform dispersion in the crystal lattice.
The high conductivity of the material is achieved, rich electron and ion transmission channels are built, the overall conductivity and structural stability of the material are improved, and the electrochemical sodium storage performance and cycle life of the positive electrode material of sodium ion battery is significantly improved.
Smart Images

Figure CN119725481A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of nanomaterials and electrochemical technology, and relates to a composite phosphate material modified by three-dimensional carbon nanowires with high conductivity and a preparation method thereof; in particular, it relates to a Na4(Fe x Mn y )3M z (PO4)2P2O7 / C material and preparation method thereof; the material can be used as positive electrode active material for sodium ion batteries. Background Art
[0002] The manganese iron-based sodium phosphate pyrophosphate material has a lattice that can provide Na + The three-dimensional channel for embedding / ejection has outstanding advantages such as high sodium ion diffusion coefficient, high structural stability, high operating voltage, and high thermal stability. It is considered to be one of the most promising positive electrode materials for sodium ion batteries. However, the electronic conductivity of this type of phosphate material is low. Researchers have explored many methods to try to solve this key technical problem. At present, the commonly used technical means in the industry include surface carbon coating, nano-sizing, and heteroatom doping. However, the surface carbon coating of materials by traditional methods has technical difficulties such as "discontinuous conductive network", "uneven carbon layer thickness", "carbon layer segregation", and "uneven distribution of doped atoms", making it difficult to significantly improve the electronic conductivity of the material. As far as we know, it is difficult to directly prepare a "highly conductive three-dimensional carbon nanowire" structure in sodium manganese iron phosphate pyrophosphate materials using conventional methods. In order to achieve high conductivity of the material, it is necessary to add exogenous conductive carbon fibers (such as carbon nanotubes, etc.) to improve the electronic conductivity of the surface interface. However, due to the high price and difficulty of good dispersion of carbon materials such as carbon nanotubes, it not only increases the material preparation cost, but also increases the complexity of the preparation process. In addition, increasing the amount of carbon coating will also lead to a sharp decrease in the compaction density of the material, which has a serious negative impact on the processing performance of the material. "Nanization" can improve the problem of large electrochemical polarization, but this process requires that the raw material particles of micron-sized iron phosphate and other raw materials be mechanically ground for a long time through ultrafine nano-milling equipment to reduce the raw material particle size to the level of hundreds of nanometers. This process takes a long time and consumes high energy. In short, the traditional preparation method faces the dilemma of complex process and high cost. Manufacturing companies need to invest huge manpower and material costs in process control to obtain materials with better comprehensive performance.
[0003] Through searching the existing patent literature, it is found that CN 118495495 A discloses a sodium iron pyrophosphate positive electrode material; it is synthesized by a simple sol-gel method, using oxalic acid as a chelating agent to construct a sodium iron pyrophosphate (Na4 Fe3 (PO4) 2 (P2 O7)) / carbon composite material with a three-dimensional conductive carbon network. However, the structure of the prepared material is relatively loose, and the gaps between the particles are large, which will lead to poor volume energy density; at the same time, the pore structure of the material is large and the distribution is very irregular, which will also lead to deficiencies in the uniformity of the electrolyte distribution, ion transfer efficiency, electronic conductivity and structural stability of the material. Summary of the invention
[0004] The purpose of the present invention is to provide a composite phosphate material (Na4(Fe x Mn y )3M z (PO4)2P2O7 / C) and its preparation method. The method of the present invention has a simple process and can achieve the effect of "killing two birds with one stone" through a "one pot method". It meets the requirements of green chemistry and is easy to scale up production. The material can be used as a positive electrode material for sodium ion batteries to exhibit excellent electrochemical sodium storage performance. Specifically, the "killing two birds with one stone" method proposed in the present invention can achieve the in-situ introduction of highly conductive three-dimensional carbon nanowires through an ordinary carbon source during the reaction process. At the same time, the doping ions M introduced into the solution can be evenly dispersed at the "atomic level" in the lattice. This method is a technical approach that can effectively improve the overall conductivity of the material. On the one hand, this highly conductive three-dimensional carbon nanowire can construct abundant transmission channels for the migration of electrons and ions from the core to the surface of the material, and its effect is like adding expensive highly conductive carbon nanotubes. On the other hand, Na4(Fe x Mn y )3M z The three-dimensional carbon structure between (PO4)2P2O7 particles can exert a "net-binding" effect, effectively limiting the excessive growth and agglomeration of primary crystal particles during high-temperature calcination, and achieving "nano-scaling" without the need for high-energy mechanical grinding. When applied to positive electrode materials for sodium-ion batteries, the three-dimensional "buffer net" can effectively prevent the structural damage of the electrode material caused by volume changes during the insertion / extraction of sodium ions during the charging and discharging process, effectively improving the cycle life of the electrode material. At the same time, highly conductive three-dimensional carbon nanowires can effectively optimize the diffusion path of ions and electrons, significantly increase their diffusion rate in the electrode, and fully realize the electrochemical performance of the active material, making Na4(Fe x Mn y )3M zAs an excellent positive electrode active material, (PO4)2P2O7 / C material promotes the commercialization of high-performance, long-life and low-cost sodium-ion batteries.
[0005] To achieve the above object, the present invention specifically provides the following technical solutions:
[0006] <First aspect>
[0007] The present invention provides a Na4(Fe2O3) modified three-dimensional carbon nanowire with high conductivity. x Mn y )3M z (PO4)2P2O7 / C material (the nanomaterial is a heteroatom-doped manganese-iron-based sodium pyrophosphate (Na4(Fe x Mn y )3M z (PO4)2P2O7) and carbon (C) complex), the salient features of the material structure are: Na4(Fe x Mn y )3M z The surface of the (PO4)2P2O7 primary particles is coated with a (uniform) nanocarbon layer, and they are highly interconnected by (tight) three-dimensional continuous (highly conductive) carbon nanowires. x Mn y )3M z The (PO4)2P2O7 primary crystal particles are (tightly) wrapped in a conductive network constructed by rich three-dimensional carbon nanowires. This material has excellent electronic and ionic conductivity and can be used as a high-performance sodium-ion battery positive electrode active material.
[0008] As an embodiment of the present invention, the Na4(Fe x Mn y )3M z The mass ratio of (PO4)2P2O7 and C is 95:5-99:1.
[0009] As one embodiment of the present invention, 0.93≤x+y≤1, and 0≤x≤1, 0≤y≤1, 0≤z≤0.2.
[0010] As one embodiment of the present invention, M is a transition metal doping ion.
[0011] As one embodiment of the present invention, M is Mg 2+ 、Ni 2+ 、Al 3+ 、V 3+ , W 3+ , Ga 3+ ,La 3+ , Y 3+ , Yb3+ Sn 4+ 、Zr 4+ , Nb 5+ 、Mo 6+ At least one of the ions.
[0012] As an embodiment of the present invention, the Na4(Fe x Mn y )3M z The particle size of the primary crystal particles of (PO4)2P2O7 is 0.2-0.5 microns.
[0013] As an embodiment of the present invention, the material is prepared by uniformly mixing raw sodium source compound, iron source compound, phosphorus source compound and reducing agent, followed by crystallization, shaping and calcination.
[0014] <Second Aspect>
[0015] The present invention provides a method for preparing a highly conductive three-dimensional carbon nanowire-modified composite phosphate material, wherein the material is Na4(Fe x Mn y )3M z (PO4)2P2O7 / C material, wherein 0.93≤x+y≤1, 0≤x≤1, 0≤y≤1, 0≤z≤0.2, and M is a transition metal doping ion; the method comprises the following steps:
[0016] S1, adding water to a transition metal source and a reducing agent and stirring until they are completely dissolved; the transition metal source comprises at least one of a manganese source, an iron source, and an M source;
[0017] S2, then add the sodium source and phosphorus source, stir until completely dissolved, to obtain a mixed solution A;
[0018] S3, add ammonia water to the mixed solution A, and adjust the pH of the solution to a state close to that of hydrogen phosphate (M z Fe 3x Mn 3y )·(HPO4)4·nH2O precipitation reaction occurs, and a metastable precursor solution B mixed with sodium ions and transition metal phosphate compounds is obtained;
[0019] S4, add a polar aprotic solvent to the precursor solution B, and form a solution containing Na4[(M z Fe 3x Mn 3y )·(HPO4)4·nH2O] component to obtain suspension C;
[0020] S5, drying the suspension C to obtain a precursor powder; calcining the precursor powder under an inert atmosphere (nitrogen, argon, etc.) to obtain Na4(Fe x Mn y )3M z (PO4)2P2O7 / C material.
[0021] As an embodiment of the present invention, the manganese source is at least one of a water-soluble organic manganese salt and an inorganic manganese salt. In some embodiments, the manganese source includes at least one of citric acid chelated manganese, sodium manganese ethylenediaminetetraacetate, manganese nitrate, manganese sulfate, and manganese acetate.
[0022] As an embodiment of the present invention, the iron source is at least one of a water-soluble organic iron salt and an inorganic iron salt. In some embodiments, the iron source includes at least one of ferric citrate, sodium ferric ethylenediaminetetraacetate, ferrous citrate, ammonium ferric citrate, ferrous nitrate, ferrous sulfate, ferrous sulfate, ferric nitrate, ammonium ferrous sulfate, and ferric acetate.
[0023] As one embodiment of the present invention, the M source is a 2+ 、Ni 2+ 、Al 3+ 、V 3+ , W 3+ , Ga 3+ ,La 3+ , Y 3 + , Yb 3+ Sn 4+ 、Zr 4+ , Nb 5+ 、Mo 6+ At least one of an inorganic salt or an organic compound soluble in water.
[0024] As an embodiment of the present invention, the reducing agent is an organic compound with a low carbonization temperature and a reducing chemical group. In some embodiments, the reducing agent includes at least one of glucose, fructose, lactose, ascorbic acid, and citric acid.
[0025] As an embodiment of the present invention, the phosphorus source is at least one of phosphoric acid, phosphorous acid, ammonium dihydrogen phosphate, and sodium dihydrogen phosphate.
[0026] As an embodiment of the present invention, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium citrate, sodium oxalate, sodium acetate, sodium tripolyphosphate, sodium tetrapolyphosphate, sodium pyrophosphate, sodium hexametaphosphate, sodium aminotri(methylene)phosphonate, sodium diethylenetriamine penta(methylene)phosphonate, sodium hydroxyethylidene diphosphonate and sodium nitrate.
[0027] As an embodiment of the present invention, the polar aprotic organic solvent is miscible with water. In some embodiments, the polar aprotic organic solvent is at least one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), acetone (C3H6O), isopropyl ketone, acetonitrile (C2H3N), pyridine (C5H5N), ethylene glycol, and ethanol.
[0028] As an embodiment of the present invention, in step S1, the molar ratio of the transition metal element to the reducing agent is an optimal value to achieve sufficient reduction of the transition metal element. In some embodiments, the molar ratio of the transition metal element to the reducing agent is 1:0.2-1:5.
[0029] As an embodiment of the present invention, in step S2, the molar ratio of the phosphorus source to the transition metal source is such that a dihydrogen phosphate (Fe 2 O 2 ) having a stoichiometric ratio of the transition metal source to the phosphorus source is obtained. x Mn y M z In some embodiments, the molar ratio of the manganese-iron transition metal source to the phosphorus source is 3:4. The molar ratio of the manganese-iron transition metal source to the sodium source is 3:4.
[0030] As an embodiment of the present invention, in step S3, the ammonia water is any one of concentrated ammonia water (25-28%) or diluted ammonia water.
[0031] As an embodiment of the present invention, in step S3, the pH of the solution is raised to 2-5. In this process, the hydroxide ions (OH-) dissociated from the ammonia water react with a hydrogen ion (H+) in the dihydrogen phosphate in the solution to neutralize, so that the solution state is close to that of the dihydrogen phosphate (M z Fe 3x Mn 3y )·(HPO4)4·nH2O) precipitation reaction occurs to obtain a metastable precursor solution B in which sodium ions and transition metal phosphate compounds are uniformly mixed.
[0032] In step S4, the solubility of the inorganic salt ions in the aqueous solution is reduced by mixing the polar aprotic solvent with water, thereby promoting the equilibrium of the precipitation reaction to move to form a solution containing (Na4[(M z Fe 3x Mn 3y )·(HPO4)4·nH2O]) component.
[0033] As an embodiment of the present invention, in step S4, the volume ratio of the polar aprotic solvent to the precursor solution B is 1:1-10:1
[0034] As an embodiment of the present invention, in step S5, the drying method is any one of hot air drying, spray drying, drum drying, vacuum drying, infrared drying, or a combination thereof.
[0035] As an embodiment of the present invention, in step S5, the organic solvent vapor is recovered and recycled during the drying process.
[0036] As an embodiment of the present invention, in step S5, the calcination temperature is 500-700°C (including all heating and cooling rates) and the calcination time is 2-20 hours.
[0037] <Third Aspect>
[0038] The use of the aforementioned highly conductive three-dimensional carbon nanowire-modified composite phosphate material, or the highly conductive three-dimensional carbon nanowire-modified composite phosphate material prepared by the aforementioned method as a positive electrode active material for a sodium ion battery also falls within the protection scope of the present invention.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] (1) Through a simple solution method combined with a solid-phase sintering method, Na4(Fe x Mn y )3M z (PO4)2P2O7 / C material.
[0041] (2) All raw materials can be dissolved in water, ensuring that various ion sources are evenly mixed at the molecular level, and the prepared material has good consistency.
[0042] (3) By mixing organic solvents with water to construct a confined structure of a "solvent cage", and by using the addition of organic solvents to rapidly reduce the solubility of inorganic salts as a driving force, the sodium ions, transition metal ions and phosphate ions in the aqueous solution can be precipitated into submicron crystals with components that conform to the stoichiometric ratio within the limited space of the nanoscale "solvent cage". The particles are closely distributed, the particle size is uniform, and the packing density is high. This can effectively solve the pain points of high energy consumption and long time caused by the traditional method of "nano-sizing" of raw materials, which must be achieved through ultrafine mechanical grinding.
[0043] (4) Through the "microphase separation" effect after the organic solvent and water are mixed, the solution is dried and then carbonized with a common reducing agent carbon source to obtain a highly conductive three-dimensional continuous carbon nanowire network. There is no need to introduce expensive exogenous conductive carbon such as carbon nanotubes. Relying on its own unique three-dimensional carbon nanowire network, the overall electronic conductivity of the material can be greatly improved.
[0044] (5) When used as a positive electrode active material for sodium ion batteries, it has ultra-high rate performance and ultra-long cycle life, and has outstanding comprehensive sodium storage performance. This method is easy to scale up production, has no pollutant emissions, has high atomic utilization, conforms to the characteristics of green chemistry, and is conducive to market promotion.
[0045] (6) The present invention shows obvious advantages in terms of microstructure density, pore structure and carbon filament structure of the material, which are helpful to improve the performance of sodium ion batteries, including energy density, rate performance and cycle stability. Specifically, it is manifested as follows: a. Structural density: The electron microscope image of the material of the present invention ( Figure 2 ) The positive electrode material exhibited has a high structural density, clear boundaries between particles, and close arrangement of particles, which is a beneficial result of the special effect of organic solvent and water. This dense structure helps to improve the volume energy density of the material, because the close arrangement of particles can reduce the voids inside the material. b. Pore structure: The material prepared by the present invention shows a highly uniform pore structure, with moderate pore size and uniform distribution, which is a beneficial result of the special effect of organic solvent and water. This pore structure is conducive to the penetration of electrolyte and the transmission of ions, thereby improving the rate performance and cycle stability of the battery. C. Carbon filament structure: The interior of the material prepared by the present invention can be seen to have an obvious carbon nanowire structure similar to carbon nanotubes. These carbon filaments have two significant characteristics: A. The diameter is at the nanometer level and the length is at the submicron level B. The number is very rich, the degree of cross-linking is very high, and it presents a true three-dimensional network structure. These can provide sufficient transmission paths for electron conduction inside the particles, significantly improve the electronic conductivity of the material, and the presence of the carbon filament network may also enhance the structural stability of the material and reduce the volume expansion during the cycle. Other carbon nanowire structures that do not meet the two characteristics AB will not be as good as the electronic conductivity and structural stability of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0047] Figure 1 The highly conductive three-dimensional carbon nanowire modified Na4(Fe 2.85 Mn 0.1 Mg 0.05 XRD spectrum of )(PO4)2P2O7 / C material;
[0048] Figure 2 The highly conductive three-dimensional carbon nanowire modified Na4(Fe 2.85 Mn 0.1 Mg 0.05)(PO4)2P2O7 / C material SEM image; wherein, the upper left is a 1k-fold magnification, the upper right is a 10k-fold magnification, the lower left is a 40k-fold magnification of the particle's internal cross section, and the lower right is a 160k-fold magnification of the large particle's internal cross section and an illustration of the existence of a three-dimensional continuous conductive carbon nanowire network and primary particles therein;
[0049] Figure 3 The highly conductive three-dimensional carbon nanowire modified Na4(Fe 2.85 Mn 0.1 Mg 0.05 )(PO4)2P2O7 / C material charge and discharge characteristic curves at different rates; the black, red, green, blue, cyan, and pink curves represent the test results at 0.2C, 1C, 2C, 5C, 10C, and 20C rates, respectively;
[0050] Figure 4 The highly conductive three-dimensional carbon nanowire modified Na4(Fe 2.85 Mn 0.1 Mg 0.05 The charge-discharge characteristic curves of (PO4)2P2O7 / C material at the 1C rate at the 1st and 1000th cycles;
[0051] Figure 5 The highly conductive three-dimensional carbon nanowires modified Na4(Mn 1.8 Fe 0.96 Nb 0.04 XRD spectrum of )(PO4)2P2O7 / C material;
[0052] Figure 6 The highly conductive three-dimensional carbon nanowires modified Na4(Mn 1.8 Fe 0.96 Nb 0.04 SEM image of )(PO4)2P2O7 / C material;
[0053] Figure 7 The highly conductive three-dimensional carbon nanowires modified Na4(Mn 1.8 Fe 0.96 Nb 0.04 )(PO4)2P2O7 / C material charge and discharge characteristic curve at 0.1C rate;
[0054] Figure 8 The Na4(Mn 1.8 Fe 0.96 Nb 0.04 SEM image of )(PO4)2P2O7 / C material. DETAILED DESCRIPTION
[0055] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0056] Example 1
[0057] This embodiment provides a highly conductive three-dimensional carbon nanowire-modified Na4(Fe 2.85 Mn 0.1 Mg 0.05 The preparation method of (PO4)2P2O7 / C material comprises the following steps:
[0058] 1) 187 g glucose (C6H 12 06) and 5g of citric acid as a reducing agent were dissolved in 2L of deionized water, and after they were completely dissolved, 834.03g of ferrous sulfate heptahydrate, 16.90g of manganese sulfate monohydrate, and 12.3g of magnesium sulfate heptahydrate were added, and the mixture was stirred for 10 minutes to obtain a clear and transparent light green solution;
[0059] 2) Measure 273 mL of 85% phosphoric acid (H3PO4) solution, add the phosphoric acid dropwise into the light green solution obtained in step 1) to make the molar ratio of the iron source, manganese source and phosphorus source 3:4, and stir evenly;
[0060] 3) Weigh 328.14 g of sodium acetate and dissolve it in the solution obtained in step 2), at which point the pH value of the solution is 1.8;
[0061] 4) under stirring, adding ammonia water diluted to 10% by mass into the solution dropwise until the pH value of the solution rises to 4.1, thereby obtaining a precursor solution thermodynamically close to the boundary where the precipitation reaction occurs;
[0062] 5) 6 L of polar aprotic solvent dimethyl sulfoxide (DMSO) was added dropwise to the precursor solution, and stirring was continued for 15 min after the addition was completed to obtain a suspension containing structurally stable submicron precursor crystals;
[0063] 5) drying and granulating the precursor microcrystalline suspension through a closed cycle spray dryer to obtain a brown precursor powder;
[0064] 6) The precursor powder was heated to 600° C. in a nitrogen atmosphere and kept at this temperature for 10 hours to obtain the highly conductive three-dimensional carbon nanowire-modified Na4(Fe 2.85 Mn 0.1 Mg 0.05)(PO4)2P2O7 / C material.
[0065] The product obtained in this example was subjected to powder X-ray diffraction analysis (see Figure 1 ), the results showed that the obtained product was 2.85 Mn 0.1 Mg 0.05 )(PO4)2P2O7 / C standard sample PDF card (89-0579) is consistent with the standard sample PDF card (89-0579), and has high crystallinity and no impurities. Figure 2 The scanning electron microscope image of the product obtained in this example shows that the product has good structural consistency. 2.85 Mn 0.1 Mg 0.05 The primary crystal particles of )(PO4)2P2O7 are tightly packed and efficiently interconnected through a three-dimensional conductive carbon nanowire network, which can effectively enhance the electronic conductivity of the material. The prepared material is used to prepare the positive electrode sheet according to the mass ratio of active material, conductive carbon and polyvinylidene fluoride (PVDF) of 8:1:1. Metallic sodium is used as the negative electrode, glass fiber is used as the separator, and the electrolyte is 1 mol / L sodium hexafluorophosphate and the solvent volume ratio is 3:2 of propylene carbonate and ethyl methyl carbonate (NaPF6 / PC+EMC). The half-cell is assembled for charge and discharge tests. The test conditions are constant current charge and discharge tests, and the voltage range is 2.0-4.3V. Figure 3 The highly conductive three-dimensional carbon nanowires modified Na4(Fe 2.85 Mn 0.1 Mg 0.05 )(PO4)2P2O7 / C charge and discharge curves of electrode materials at different current densities. At current densities of 0.2, 1, 2, 5, 10, and 20C, the reversible discharge specific capacity of the electrode material can reach 105, 104, 104, 103, 102, and 98.5 mAh g, respectively. -1 At a high current density of 20C (i.e., a charge is completed in 3 minutes), the specific capacity can still be maintained at nearly 94% relative to that at a current density of 0.2C, indicating that the material has excellent high-rate fast charge and discharge performance. From the charge and discharge curve, it can be seen that the voltage polarization of the material is small and the voltage platform is well maintained, indicating that the material has excellent electronic conductivity. Figure 4 It shows that at a current density of 1C, after 1000 cycles, the capacity retention rate is close to 100%, and the voltage platform has almost no attenuation, indicating that it has very outstanding structural stability and low resistance interface. The above results show that thanks to the unique structure of submicron-sized crystal particles coupled with highly conductive three-dimensional carbon nanowire network constructed by this new preparation method, it can ensure the stability of sodium manganese iron pyrophosphate Na4 (Fe 2.85 Mn 0.1 Mg0.05 )(PO4)2P2O7 / C material has excellent rate performance, capacity performance and cycle life.
[0066] Example 2
[0067] This embodiment provides a highly conductive three-dimensional carbon nanowire-modified Na4(Mn 1.8 Fe 0.96 Nb 0.04 The preparation method of (PO4)2P2O7 / C material comprises the following steps:
[0068] 1) 104 g of fructose and 10 g of ascorbic acid as reducing agents were dissolved in 2 L of deionized water, and after they were completely dissolved, 700.43 g of sodium manganese ethylenediaminetetraacetate, 266.93 g of ferrous sulfate heptahydrate, and 21.5216 g of niobium oxalate were added, and the mixture was stirred for 30 minutes to obtain a clear and transparent light yellow-green solution;
[0069] 2) Measure 252 mL of 85% phosphoric acid (H3PO4) solution, add the phosphoric acid dropwise into the light yellow-green solution obtained in step 1) so that the molar ratio of the transition metal source to the phosphorus source is 3:4, and stir evenly;
[0070] 3) Weigh 38.70 g of sodium aminotri(methylenephosphonate) and dissolve it in the solution obtained in step 2), at which point the pH value of the solution is 1.9;
[0071] 4) under stirring, adding ammonia water diluted to 15% by mass into the solution dropwise until the pH value of the solution rises to 4.3, thereby obtaining a precursor solution thermodynamically close to the boundary where the precipitation reaction occurs;
[0072] 5) Add 5 L of polar aprotic solvent N,N-dimethylformamide (DMF) to the precursor solution, and continue stirring for 30 minutes after the addition to obtain a suspension containing structurally stable nanoscale precursor microcrystals;
[0073] 5) drying the precursor microcrystalline suspension by a closed air blower dryer to obtain a brown precursor powder;
[0074] 6) The precursor powder was heated to 650° C. and kept at this temperature for 10 hours under an argon atmosphere to obtain the highly conductive three-dimensional carbon nanowire-modified Na4(Mn 1.8 Fe 0.96 Nb 0.04 )(PO4)2P2O7 / C material.
[0075] The product obtained in this example was subjected to powder X-ray diffraction analysis (see Figure 5 ), it can be seen that the material has good crystallinity and phase purity. Figure 6The scanning electron microscope image of the product obtained in this example shows that although regular spherical particles were not prepared by spray drying, Na4(Mn 1.8 Fe 0.96 Nb 0.04 The primary crystal particles of )(PO4)2P2O7 / C are tightly packed, and the microstructure maintains the characteristics of a three-dimensional network structure with rich pores and denseness, which provides good penetration and mass transfer performance for the contact between the electrolyte and the active material. The electronic conductivity of the material is effectively guaranteed, and the electrochemical performance of the material can be fully exerted. The charge and discharge curve of the button-type sodium ion half-cell assembled with it as the positive electrode active material at 0.1C is shown in the figure below: Figure 7 As shown, the discharge specific capacity is 102mAh / g, the energy density is as high as 360Wh / kg, and the capacity retention rate after 200 cycles is greater than 95%.
[0076] Example 3
[0077] This embodiment provides a highly conductive three-dimensional carbon nanowire-modified Na4(Mn 1.8 Fe 0.96 V 0.07 The preparation method of (PO4)2P2O7 / C material comprises the following steps:
[0078] 1) 93 g of glucose and 10 g of citric acid as a reducing agent were dissolved in 2 L of deionized water, and after they were completely dissolved, 700.43 g of sodium manganese ethylenediaminetetraacetate, 352.37 g of sodium iron ethylenediaminetetraacetate, and 8.18 g of ammonium metavanadate were added, and the mixture was stirred for 30 minutes to obtain a clear and transparent light yellow solution;
[0079] 2) Add 38.99 g of phosphorous acid (H3PO3) to the light yellow solution obtained in step 1) and stir to dissolve;
[0080] 3) Weigh 40.90 g of sodium citrate and 440.56 g of disodium hydroxyethylidene diphosphonate and dissolve them in the solution obtained in step 2), at which point the pH value of the solution is 1.7;
[0081] 4) under stirring, adding ammonia water diluted to 10% by mass into the solution dropwise until the pH value of the solution rises to 4.3, thereby obtaining a precursor solution thermodynamically close to the boundary where the precipitation reaction occurs;
[0082] 5) 4.5 L of polar aprotic solvent N,N-dimethylformamide (DMF) was added dropwise to the precursor solution, and stirring was continued for 30 min after the addition was completed to obtain a suspension containing structurally stable nanoscale precursor microcrystals;
[0083] 5) drying the precursor microcrystalline suspension by a closed air blower dryer to obtain a yellow-green precursor powder;
[0084] 6) The precursor powder was heated to 650° C. and kept at this temperature for 10 hours under an argon atmosphere to obtain the highly conductive three-dimensional carbon nanowire-modified Na4(Mn 1.8 Fe 0.96 V 0.07 )(PO4)2P2O7 / C material.
[0085] The powder X-ray diffraction spectrum of the product obtained in this example was analyzed, and it can be seen that the material has good crystallinity and crystal phase purity. The morphology of the obtained product was analyzed by scanning electron microscopy, and its microstructure also maintained the characteristics of a three-dimensional network structure with rich and dense pores, and the primary crystal particles were tightly packed. The button-type sodium ion half-battery assembled with it as the positive electrode active material was charged and discharged at a rate of 0.1C, and the discharge specific capacity was 103.6mAh / g, the energy density was as high as 362Wh / kg, and the capacity retention rate was maintained at more than 99% after 100 cycles.
[0086] Comparative Example 1
[0087] This comparative example is Na4(Mn 1.8 Fe 0.96 Nb 0.04 )(PO4)2P2O7 / C nanomaterial, the following steps:
[0088] 1) 104 g of fructose and 10 g of ascorbic acid as reducing agents were dissolved in 2 L of deionized water, and after they were completely dissolved, 700.43 g of sodium manganese ethylenediaminetetraacetate, 266.93 g of ferrous sulfate heptahydrate, and 21.5216 g of niobium oxalate were added, and the mixture was stirred for 30 minutes to obtain a clear and transparent light yellow-green solution;
[0089] 2) Measure 252 mL of 85% phosphoric acid (H3PO4) solution, add the phosphoric acid dropwise into the light yellow-green solution obtained in step 1) so that the molar ratio of the transition metal source to the phosphorus source is 3:4, and stir evenly;
[0090] 3) Weigh 38.70 g of sodium aminotri(methylenephosphonate) and dissolve it in the solution obtained in step 2), at which point the pH value of the solution is 1.9;
[0091] 4) under stirring, adding ammonia water diluted to 15% by mass into the solution dropwise until the pH value of the solution rises to 4.3, thereby obtaining a precursor solution thermodynamically close to the boundary where the precipitation reaction occurs;
[0092] 5) drying the precursor solution by a closed air blower dryer to obtain a brown precursor lump;
[0093] 6) After the precursor block was ground into powder in a mortar, the temperature was raised to 650°C and kept for 10 hours under a nitrogen atmosphere to obtain Na4(Mn 1.8 Fe 0.96 Nb 0.04 )(PO4)2P2O7 / C material.
[0094] Figure 8 The scanning electron microscope image of the product obtained in the comparative example shows that its morphology and structure have changed significantly compared with the material prepared in Example 2. Due to the lack of the "solvent cage" effect of the non-protonic polar solvent and the aqueous solution, the primary crystal particle growth process lacks effective restrictions, resulting in a significant increase in its particles, and the crystal morphology presents an irregular geometric structure; on the other hand, due to the lack of the "microphase separation" effect of the mixed solvent, the reducing agent does not form a rich three-dimensional conductive carbon network around the primary crystal particles after carbonization, and part of the carbon exists in the form of separate segregation. This structure causes the material to not have good electronic and ionic conductivity. The button-type sodium ion half-battery assembled with it as the positive active material has a discharge capacity of only 82mAh / g at 0.1C, and the capacity retention rate after 100 cycles of energy-dense cycles is only 65%.
[0095] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A highly conductive three-dimensional carbon nanowire-modified composite phosphate material, characterized in that: The material is Na4(Fe x Mn y )3M z (PO4)2P2O7 / C material, in which Na4(Fe x Mn y )3M z The surface of the (PO4)2P2O7 primary particles is coated with a nanocarbon layer, and the primary particles are connected to other adjacent primary particles through three-dimensional carbon nanowires.
2. The composite phosphate material according to claim 1, characterized in that: It includes at least one of the following technical features: A1, Na4(Fe x Mn y )3M z The mass ratio of (PO4)2P2O7 and C is 95:5-99:1; A2, 0.93≤x+y≤1, and 0≤x≤1, 0≤y≤1, 0≤z≤0.2; A3, M are transition metal doping ions; A4, M is Mg 2+ 、Ni 2+ 、Al 3+ 、V 3+ , W 3+ , Ga 3+ ,La 3+ , Y 3+ , Yb 3+ Sn 4+ 、Zr 4+ , Nb 5+ 、Mo 6+ At least one of the ions; A5, the Na4(Fe x Mn y )3M z The particle size of the primary crystal particles of (PO4)2P2O7 is 0.2-0.5 microns.
3. A method for preparing a highly conductive three-dimensional carbon nanowire-modified composite phosphate material, characterized in that: The material is Na4(Fe x Mn y )3M z (PO4)2P2O7 / C material, wherein 0.93≤x+y≤1, 0≤x≤1, 0≤y≤1, 0≤z≤0.2, and M is a transition metal doping ion; the method comprises the following steps: S1, adding water to a transition metal source and a reducing agent and stirring until they are completely dissolved; the transition metal source comprises at least one of a manganese source, an iron source, and an M source; S2, then add the sodium source and phosphorus source, stir until completely dissolved, to obtain a mixed solution A; S3, add ammonia water to the mixed solution A, and adjust the pH of the solution to a state close to that of hydrogen phosphate (M z Fe 3x Mn 3y )·(HPO4)4·nH2O precipitation reaction occurs, and a metastable precursor solution B mixed with sodium ions and transition metal phosphate compounds is obtained; S4, add polar aprotic solvent to the precursor solution B, and form a solution containing Na4[(M z Fe 3x Mn 3y )·(HPO4)4·nH2O] component to obtain suspension C; S5, drying the suspension C to obtain a precursor powder; calcining the precursor powder under an inert atmosphere to obtain Na4(Fe x Mn y )3M z (PO4)2P2O7 / C material.
4. The method for preparing the composite phosphate material according to claim 3, characterized in that: Include at least one of the following technical features: B1. The manganese source is at least one of a water-soluble organic manganese salt and an inorganic manganese salt; B2, the manganese source includes at least one of citric acid chelated manganese, sodium manganese ethylenediaminetetraacetate, manganese nitrate, manganese sulfate, and manganese acetate; B3, the iron source is at least one of a water-soluble organic iron salt and an inorganic iron salt; B4, the iron source includes at least one of ferric citrate, sodium ferric ethylenediaminetetraacetate, ferrous citrate, ammonium ferric citrate, ferrous nitrate, ferrous sulfate, ferrous sulfate, ferric nitrate, ammonium ferrous sulfate, and ferric acetate; B5, the M source contains Mg 2+ 、Ni 2+ 、Al 3+ 、V 3+ , W 3+ , Ga 3+ ,La 3+ , Y 3+ , Yb 3+ Sn 4+ 、Zr 4+ , Nb 5+ 、Mo 6+ At least one of an inorganic salt or an organic compound soluble in water.
5. The method for preparing the composite phosphate material according to claim 3, characterized in that: Include at least one of the following technical features: C1. The reducing agent is an organic compound with a low carbonization temperature and a reducing chemical group; C2, the reducing agent includes at least one of glucose, fructose, lactose, ascorbic acid, and citric acid; C3, the phosphorus source is at least one of phosphoric acid, phosphorous acid, ammonium dihydrogen phosphate, and sodium dihydrogen phosphate; C4, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium citrate, sodium oxalate, sodium acetate, sodium tripolyphosphate, sodium tetrapolyphosphate, sodium pyrophosphate, sodium hexametaphosphate, sodium aminotri(methylenephosphonic acid), sodium diethylenetriamine penta(methylenephosphonic acid), sodium hydroxyethylidene diphosphonic acid and sodium nitrate; C5, the polar aprotic organic solvent is miscible with water; C6. The polar aprotic organic solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, acetone, isopropyl ketone, acetonitrile, pyridine, ethylene glycol and ethanol.
6. The method for preparing the composite phosphate material according to claim 3, characterized in that: In step S1, the molar ratio of the transition metal element to the reducing agent is based on achieving sufficient reduction of the transition metal element.
7. The method for preparing the composite phosphate material according to claim 3, characterized in that: In step S2, the molar ratio of the phosphorus source to the transition metal source is such that a dihydrogen phosphate (Fe x Mn y M z (H2PO4)2) solution shall prevail.
8. The method for preparing the composite phosphate material according to claim 3, characterized in that: In step S4, the volume ratio of the polar aprotic solvent to the precursor solution B is 1:1-10:1; and / or, in step S1, the molar ratio of the transition metal element to the reducing agent is 1:0.2-1:
5.
9. The method for preparing the composite phosphate material according to claim 3, characterized in that: In step S5, the calcination temperature is 500-700° C., and the calcination time is 2-20 hours.
10. Use of the composite phosphate material according to claim 1 or 2, or the composite phosphate material obtained by the method according to any one of claims 3 to 9 as a positive electrode active material for a sodium ion battery.
Citation Information
Patent Citations
Carbon-coated sodium manganese phosphate pyrophosphate@SWCNT (Single Walled Carbon Nanotube) composite material with net structure and preparation and application thereof
CN110085849A
Dual-carbon modified iron-manganese-based mixed phosphate microsphere material as well as preparation method and application thereof
CN117613227A
Tremella-like ferric sodium pyrophosphate composite material as well as preparation method and application thereof
CN118929615A
Positive electrode material and preparation method therefor, battery, energy storage device and energy storage system
WO2024120092A1